Construction and clinical application of "One Syndrome and One Product" nursing program for patients with lumbar disc herniation (腰椎间盘突出症"一证一品"护理方案的构建与临床应用) - ZHANG Xuejian (张雪键); TANG Ling (唐玲); ZHANG Dahua (张大华); ZHANG Jing (张敬); TANG Yue (唐月) (Journal of International Translational Medicine Limited, 2021)
Objective To establish the "One Syndrome and One Product" nursing program in clinical practice, and to investigate clinical effect of "one syndrome and one product" nursing program in patients with lumbar disc herniation(LDH). Methods Through literature analysis, evidence-based nursing, clinical trial study and other methods, the nursing program of "One Syndrome and One Product" for LDH was constructed. Totally 66 LDH patients with hospital admission date between January and December 2018 and treated by conservative therapy were included in the control group. Another 66 LDH patients with hospital admission date between January and December 2019 and s treated by conservative therapy were included in the observation group. Patients in the control group received routine care during hospitalization, and those in the observation group received "one syndrome and one product" nursing program. The degree of pain relief, awareness of health education, degree of satisfaction and severity of constipation were measured and compared between two groups. Results There were 3 cases in the observation group and 4 cases in the control group failed to follow up. Compared with the control group, the degree of pain relief and severity of constipation in the observation group were significantly reduced(P<0. 01), and the awareness of health education and degree of satisfaction were significantly increased(P<0. 01). Conclusion The nursing program of "one syndrome and one product" is potentially effective to reduce the degree of pain symptoms and incidence of constipation, improve patient awareness of health education and degree of satisfaction in LDH patients. (目的 通过构建腰椎间盘突出症"一证一品"护理方案并在临床中应用, 探讨腰椎间盘突出症"一证一品"护理方案临床实践效果。方法 采用文献分析、循证护理、临床试验研究等方法, 构建腰椎间盘突出症"一证一品"护理方案, 选取2018年1月-2019年12月在本院骨伤中心住院的132例腰椎间盘突出症且选择保守治疗的患者作为研究对象, 将2018年1月-12月收治的66例患者纳入对照组, 采用常规护理; 将2019年1月-12月收治66例患者纳入观察组, 采用"一证一品"护理方案。对2组疼痛症状缓解程度、健康教育知晓情况、患者满意度、便秘发生程度共4个维度进行评价。结果 观察组63例和对照组62例患者完成研究。与对照组相比, 观察组疼痛症状缓解程度、便秘发生程度均降低(P＜0. 01), 健康教育知晓程度和满意度均提高, 差异有统计学意义(P＜0. 01)。结论 构建腰椎间盘突出症 "一证一品"护理方案并在临床中应用, 能有效降低腰椎间盘突出症患者疼痛症状和便秘发生风险, 提高健康教育知晓率和住院服务满意度。)